Women's experiences of hospital delivery at Chiradzulu District Hospital, Malawi - Phiri Kabango, Colette (2021)
The number of pregnant women who fall ill and die due to pregnancy related complications is rising each year. In response to this, skilled birth attendance was identified by the United Nations as an indicator for monitoring progress of Millennium Development Goal number five, that could be used to assist in lowering maternal and neonatal morbidity and mortality. However, evidence has shown that other women are giving birth away from Chiradzulu District Hospital where skilled birth attendants are available. This study aimed to explore child birth experiences of women who delivered at the health facility in order to develop informed midwifery interventions that will motivate women to give birth at a health facility. A descriptive qualitative research method was used. The target group was postnatal women who had delivered normally and had stayed at the health facility for not more than 48 hours. A total of 20 participants were recruited for the study using purposive sampling method. Qualitative data was collected through in-depth interviews using a semi-structured interview guide and the interviews were audio recorded. Data were analysed using thematic analysis. The following themes were identified; perceptions of health facility care, satisfaction with health facility care and expectations of health facility care. There is need to develop operational interventions that would address pregnant women’s needs at the health facility in order to increase its utilization for maternity services.